Changes in functional state of students under the influence of physical education and apiotherapy. - Chernienko A.A; Grigus I.M (Kharkov National Pedagogical University, 2010)
The data on the use of physical education in conjunction with apiotherapy for improving the functional state of students. The study has brought improvement in the respiratory and cardiovascular systems of the body of students under the influence of the proposed program of physical education in conjunction with apiotherapy and nutrition. It is bringing a positive influence of physical training in combination with apiotherapy on functional status in children high school age.